Pred-away / Adham Mozzad Mohd Riza...[et al.] - Mohd Riza, Adham Mozzad; Mohd Nazeri, Irdina; Mohd Azmi, Nur Liyana; Mohd Hamzani, Syahmirul Haziq; Mohd Nor, Nur Syahira; Azman, Mahathir (2018)
This business plan is a new projected business that has been named as Vital Force Sdn. Bhd. The name of the company came from the partnerships of the company itself. We supply the latest and up-to-date technologies to the customers